PERLINDUNGAN TERHADAP WARGA SIPIL SEBAGAI KORBAN PENYANDERAAN DALAM KONFLIK BERSENJATA DI FILIPINA MENURUT HUKUM HUMANITER INTERNASIONAL - Anggie Sere Sitompul; Sulaiman Hamid; Chairul Bariah (Journal of USU International Law, 2014)
ABSTRACT Protection of civilians Moro as victims of hostage in an armed conflict in the Philippines into the spotlight sharper international law. Hostage-taking carried out by MNLF result as a form of rebellion against the Central Government of the Philippines over the Government's actions which only involves the MILF in the negotiations concerning the framework of the peace with the Moro Islamic Liberation Front, which was held in Malaysia in August 2013. The problems in this research are: how the act of a standoff against civilians in armed conflict viewed from humaniter international law, how a solution that can be taken in the act of a standoff civilians in the armed conflict, and how renewed efforts by the philippines in dealing with the act of a standoff civilians in the armed conflict in the government of Southern Philippines. This research is a juridical normative because the target of research is reviewing the rule of law that is related to the protection of civilians as a sacrifice captivity in armed conflict in the Philippines according to law humaniter international by using the library techniques. Data were analyzed qualitatively. Protection against civilians in armed conflict according to law humaniter international arranged in The Geneva Convention IV with Additional Protocol II and International Customs Law Humaniter.The conflict that took place in the Philippines at first due to the distinction between history and understand the Central Government of the Philippines with the separatist movements in the country, and the conflict has intensified because of the actions of the Philippines Government which judged less prudent in doing the negotiating efforts with the rebels. The legal consequences for the perpetrators of the hostage-taking of civilians in armed conflict under the law or international sanctions humaniter can be meted out to the perpetrators of the hostage-taking of civilians is given in accordance with the national law in force in each country. Keywords: Non-International Armed Conflicts, Hostage-Taking, The Moro, The Philippines, The Geneva Conventions, The Laws Of Humaniter.